INOVASI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM MELALUI MODEL CONTEXTUAL TEACHING AND LEARNING DALAM MENINGKATKAN TARAF BERPIKIR PESERTA DIDIK - Tatang Hidayat; Syahidin Syahidin (Department of Islamic Education, The State Islamic University Sunan Kalijaga Yogyakarta, 2019)
The purpose of this discussion is to describe learning innovations in Islamic Religious Education through the Contextual Teaching and Learning model to improve students' level of thinking. This discussion employs a qualitative approach and literature study method. Based on the results of the discussion, the Contextual Teaching and Learning model is a learning model which have students get involved in relating the material learned to the real life context. The Contextual Teaching and Learning model accommodates the involvement of students physically and mentally. Accordingly, the students are facilitated in developing their own knowledge which already exists in the structure of their intellective faith (aqliyah), and given the opportunity to solve problems together in scientific activities. Therefore, the Contextual Teaching and Learning model can be used as an alternative model for the process of internalizing Islamic values in learning Islamic Religious Education.